Small body size and extreme cortical bone remodeling indicate phyletic dwarfism in Magyarosaurus dacus (Sauropoda: Titanosauria) - Stein, Koen (2010)
Sauropods were the largest terrestrial tetrapods (>105 kg) in Earth's history and grew at rates that rival those of extant mammals. Magyarosaurus dacus, a titanosaurian sauropod from the Upper Cretaceous (Maastrichtian) of Romania, is known exclusively from small individuals (<103 kg) and conflicts with the idea that all sauropods were massive. The diminutive M. dacus was a classical example of island dwarfism (phyletic nanism) in dinosaurs, but a recent study suggested that the small Romanian titanosaurs actually represent juveniles of a larger-bodied taxon. Here we present strong histological evidence that M. dacus was indeed a dwarf (phyletic nanoid). Bone histological analysis of an ontogenetic series of Magyarosaurus limb bones indicates that even the smallest Magyarosaurus specimens exhibit a bone microstructure identical to fully mature or old individuals of other sauropod taxa. Comparison of histologies with large-bodied sauropods suggests that Magyarosaurus had an extremely reduced growth rate, but had retained high basal metabolic rates typical for sauropods. The uniquely decreased growth rate and diminutive body size in Magyarosaurus were adaptations to life on a Cretaceous island and show that sauropod dinosaurs were not exempt from general ecological principles limiting body size.